Thrombus on the device early after the procedure of the left atrial appendage closure with the amplatzer cardiac plug: Is something wrong with the procedure or the device? - Baris Kilicaslan; Oner Ozdogan; Ali Kemal Cabuk; Inan Mutlu (International Journal of the Cardiovascular Academy, 2019)
Percutaneous left atrial appendage (LAA) closure is a currently utilized procedure for the prophylaxis of thromboembolic cerebrovascular events in selected patients with nonvalvular atrial fibrillation. The presence of thrombus on closure device was reported at 1st and 3rd months after the procedure, but as far as our knowledge, there are no data about early thrombus formation on the device during procedure. We present a case demonstrating thrombus on the atrial side of the Amplatzer Amulet LAA occluder device early after the implantation.